Management of Impacted and Inverted Mesiodens - A Report of Two Cases - Vabitha Shetty; Rajmohan Y. Shetty; Deepshikha Mehrotra; Amina Usman; Nagashree Prabhu (Journal of Pharmacy and Bioallied Sciences)
Supernumerary teeth represent a significant dental anomaly that has a notable impact on the primary and early mixed dentition, potentially leading to pathological disturbances in the development of permanent dentition. Mesiodens specifically refers to an additional tooth (erupted/unerupted) present in the midline between the two central incisors. This article describes two cases involving the surgical extraction of inverted and impacted mesiodens by using a minimally invasive surgical approach in children. Early extraction of supernumeraries can offer the advantage of minimizing loss of eruptive potential, space loss, and midline displacement. The decision on the treatment plan should be primarily influenced by the position of the mesiodens and its proximity to the permanent incisors.